Litteratur - Knud Waaben; L. Nordskov Nielsen; Nils Christie; Kaj Arentsen; Jon Johnsen; Georg K. Stürup; A. Haslund; Preben Wolf; Stephan Hurwitz (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews